Evaluasi Anggaran dan Realisasi Biaya Operasional sebagai Instrumen Perencanaan pada PT. Perkebunan Nusantara III Kebun Bandar Selamat - Garini, Novia Ardhya; Sugianto, Sugianto; Kusmilawaty, Kusmilawaty (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This study aims to analyze operational cost budgeting as a planning tool at PT. Perkebunan Nusantara III Kebun Bandar Selamat. The research was conducted in Aek Songsongan District, Asahan Regency, North Sumatra, using a qualitative descriptive method. The data used consists of primary and secondary sources collected through interviews and document studies. The findings indicate that each year there is a positive variance between the budget and actual operational costs. In 2021, eight cost items showed a positive variance, including honorarium, production quality costs (ISO 9000), environmental control (ISO 14000), occupational health and safety management system (SMK3), as well as the use and maintenance of small inventory. Meanwhile, in 2022, six cost items recorded a positive variance, though some categories exhibited a negative variance, such as transportation expenses, off-site travel, and CSR contributions. These findings suggest that the operational cost budgeting at PT. Perkebunan Nusantara III is relatively effective; however, further optimization is needed to minimize negative variances and enhance operational cost efficiency.